2015
DOI: 10.4274/tjo.24381
|View full text |Cite
|
Sign up to set email alerts
|

External Dacryocystorhinostomy for the Treatment of Functional Nasolacrimal Drainage Obstruction

Abstract: Objectives:To determine the outcome and long-term efficacy of external dacryocystorhinostomy (ext-DCR) with or without bicanalicular silicon intubation in patients with functional nasolacrimal drainage obstruction (FNLDO).Materials and Methods:Patients with epiphora and patent lacrimal systems on nasolacrimal irrigation were prospectively enrolled in the study. Each patient was assessed with lacrimal scintigraphy to differentiate drainage abnormalities as presac (proximal) or postsac (distal) delays. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…These findings may support the multifactorial cause for epiphora, which should not be assessed only from the anatomical point of view. Noteworthy, some of these nonobstructive eyes improve after surgical intervention [23,36,[45][46][47][48][49][50]. Hence, it is of great importance to differentiate those with a favorable surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings may support the multifactorial cause for epiphora, which should not be assessed only from the anatomical point of view. Noteworthy, some of these nonobstructive eyes improve after surgical intervention [23,36,[45][46][47][48][49][50]. Hence, it is of great importance to differentiate those with a favorable surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This classification may be of relevance in decision making as well as assessment of outcome after the procedures. The successful surgery has been reported in 83.3–91% of LDS in the postsac and 47–66% in the presac patterns [47–49]; this correlation has not been observed in all studies [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simsek et al [11] demonstrated the long-term efficacy of external DCR in functional NLDO patients with presac delay. External DCR may be also effective in the management of epiphora in patients with one intact canaliculus without NLDO by facilitating lacrimal drainage.…”
Section: Discussionmentioning
confidence: 99%